2021
DOI: 10.1080/13102818.2021.1892523
|View full text |Cite
|
Sign up to set email alerts
|

Research on prediction of contact stress of acetabular lining based on principal component analysis and support vector regression

Abstract: In the "worst-case" selection of hip prosthesis wear, it is necessary to calculate the contact stress of the acetabular liner. However, there are various combinations of acetabular prostheses. If calculated one by one, it will cause a large workload, a repeated and tedious calculation problem. To solve this problem, a machine learning prediction method by combining principal component analysis and support vector regressions (PCA-SVR) was established. First, the finite element method is used to analyze and calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Their efforts were aimed at identifying the optimal prosthesis design to reduce the probability of dislocation. Similarly, Jun et al [ 30 ] used results produced using an FE model analysis to train a machine learning method that combines both principal component analysis (PCA) and support vector regression (SVR) in an effort to predict the contact stress of the hip prosthesis acetabular lining. The prediction model performance was then compared with the ridge regression and lasso models for validation.…”
Section: Introductionmentioning
confidence: 99%
“…Their efforts were aimed at identifying the optimal prosthesis design to reduce the probability of dislocation. Similarly, Jun et al [ 30 ] used results produced using an FE model analysis to train a machine learning method that combines both principal component analysis (PCA) and support vector regression (SVR) in an effort to predict the contact stress of the hip prosthesis acetabular lining. The prediction model performance was then compared with the ridge regression and lasso models for validation.…”
Section: Introductionmentioning
confidence: 99%
“…Merali et al adapted the RF model to estimate the outcome of degenerative cervical myelopathy surgery [24]. Jun et al proposed a contact stress prediction method on total hip replacement implants using principal component analysis and SVM [33]. Kruse et al reported that the XGB algorithm is capable of predicting hip fractures [34].…”
Section: Introductionmentioning
confidence: 99%
“…Tapia et al built a surrogate model by applying Gaussian processes regression (GPR) to predict the melt pool depth of the laser powder bed fusion process [14]. Numerous methods have been applied in other studies to construct surrogate models; these methods include support vector regression (SVR) [15][16][17][18], the response surface methodology [19][20][21], kriging [22][23][24][25], and the adaptive neuro fuzzy inference system (ANFIS) [26].…”
mentioning
confidence: 99%